Factores de riesgo asociados al diagnóstico de catarata en adultos de 50 a 80 años, atendidos por el servicio de Oftamología del Hospital Isidro Ayora. - Apolo Torres, Danilo Alexander (2017)
The cataract is an opacity from crystalline with the sufficient intensity to reduce the vision. The major part of cataracts are slowly formed due to aging which causes a gradual alteration of the vision. It is an important cause of ophthalmological morbidity and, at the same time, leaves a consequence for patients who suffer it. It is the main cause of blindness worldwide frequently diagnosed in primary health care services; but it is mainly presented in adults older than 50 years of age, affecting their quality of life if a diagnose and treatment is not performed at the right time. Therefore, a retrospective and cross-sectional descriptive study was performed, by achieving the following objectives: To determine the most frequent risk factors associated with the diagnosis of cataracts in patients from 50 to 80 years of age, who attended to the Ophthalmology service from “Isidro Ayora” Hospital, Establishing the level of visual acuity and the type of cataract more frequent. For the selection of patients we took into account those who were treated by cataract diagnosis in external consultation from Isidro Ayora Hospital period January to December 2014, excluding those who presented a pathology other than the one mentioned before. We studied 86 patients whose data was collected using a form that contained the variable in the study. The results showed a superiority from the female genre with a 52%, the age group corresponding to 70 and 80 years of age with a 48%. The most frequent and associated risk factors were Diabetes Mellitus II and Hypertension with a 51% and 43% respectively. The visual acuity ranges from 20/200 which represented a 53% from the right eye and 42% from the left eye. Clinically the type of cataract that was presented the most was nuclear and posterior sub capsular represented with a 36% and 26% respectively. KEY WORDS: CATARACT, RISK FACTORS, CATARACT TYPE.